2017
DOI: 10.1253/circj.cj-16-0751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MicroRNA-30e on the Behavior of Vascular Smooth Muscle Cells via Targeting Ubiquitin-Conjugating Enzyme E2I

Abstract: Background: Many microRNAs (miRNAs) have recently been shown to demonstrate critical roles in differentiation, proliferation and migration of vascular smooth muscle cells (VSMCs). Methods and Results:In this study, a certain amount of miRNA expression in VSMCs was evaluated by real-time polymerase chain reaction, and it was found that microRNA-30e (miR-30e) was expressed more strongly than other common vascular well-expressed miRNAs in vitro. Subsequently, both a gain and loss of function study was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Important roles for sumoylation were shown in heterochromatin configuration, and sumoylation of core histones negatively regulates transcription (Neyret-Kahn et al, 2013). MiR-30e-5p-induced downregulation of UBE2I inhibited the proliferation and migration of vascular smooth muscle cells (Zong et al, 2017). MUC17 is a glycoprotein characterized as a membrane-bound mucin that provides protection to gut epithelial cells (Gum et al, 2002; Luu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Important roles for sumoylation were shown in heterochromatin configuration, and sumoylation of core histones negatively regulates transcription (Neyret-Kahn et al, 2013). MiR-30e-5p-induced downregulation of UBE2I inhibited the proliferation and migration of vascular smooth muscle cells (Zong et al, 2017). MUC17 is a glycoprotein characterized as a membrane-bound mucin that provides protection to gut epithelial cells (Gum et al, 2002; Luu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a not only down-regulates Silent Information Regulator 2 homolog 1, but also promotes the expression of age-related pro-inflammatory secretory factors, thereby promoting VSMC aging [ 13 ]. Reports have also indicated that miR-23 cluster can regulate blood vessel formation [ 14 ], while miR-30e can inhibit proliferation and migration of VSMCs, promote the apoptosis thereof, and exert anti-atherosclerosis effects [ 15 ]. Moreover, by inhibiting autophagy of vascular endothelial cells and promoting cell apoptosis, miR-199a-5p has been revealed to damage vascular endothelial cells and aggravate vascular aging [ 16 ].…”
Section: The Mechanism Of Vascular Agingmentioning
confidence: 99%
“…From the identified DELs, we analyzed 33 DELs containing Argonaute 2 (AGO2) binding sites, so these lncRNAs might Construction of DELs-miRNAs interaction networks (Figure 6), indicated that HIF1A-AS2 might sponge 187 miRNAs, including miR-30e-5p (18)(19)(20), miR-25-3p (21), miR-200c-3p (5), miR-490-3p (22), and miR-34b-5p (23); these five miRNAs are demonstrated to suppress VSMC proliferation (Figure 6A). AC016747.3 might sponge 41 miRNAs, including miR-342-3p (24) that has been shown to inhibit VSMC proliferation (Figure 6B).…”
Section: Construction Of Dels-mirnas Interaction Networkmentioning
confidence: 99%